Asuhan Keperawatan Jiwa Pada Ny.T Dengan Gangguan Persepsi Sensori: Halusinasi Pendengaran Di Ruang Dewaruci RSJD dr. Amino Gondohutomo Provinsi Jawa Tengah - Rostiana Dwi Lestari; Slamet Wijaya; Tati Karyawati (Lembaga Pengembangan Kinerja Dosen, 2023)
According to WHO (World Health Organization), health is a state of complete physical, mental and social well-being, not just freedom from disease or weakness/disability. From this description it can be concluded that health implies ideal health conditions, both from a biological, psychological and social perspective. Apart from that, WHO also describes several health characteristics that need to be known, including physical and spiritual health without involving external elements, health related to the internal or external environment, spiritual health, mental health or what is usually called mental health (WHO, 2022). Mental disorders are disorders in the way of thinking (cognitive), will (volition), emotions (affective), actions (psychomotor). One of the mental disorders that greatly affects and disrupts an individual's life is schizophrenia (Makhruzah et al, 2021).